Lead market India : key elements and corporate perspectives for frugal innovations - Herstatt, Cornelius; Tiwari, Rajnish (Springer, 2017)
India is still perceived by some as a developing country that has yet to create world-class products of its own. However, this book shows that in recent years India has emerged as a lead market for frugality-driven innovations that are affordable, robust and successful even outside its geographic boundaries. Many global companies have recognized these changes and are ramping up their local R & D capabilities. At the same time, several Indian firms are venturing out to international shores and gaining access to new markets. Using a top-down approach, the book takes a closer look at systems of innovation at work and presents examples of successful, corporate innovations in multiple industries and their contextual conditions.
Keywords: Technological innovations -- India.; Technological innovations -- Economic aspects -- India.; India.; elektronické knihy; electronic books